Pharmacological Management of Chronic Neuropathic Pain – Consensus Statement and Guidelines from the Canadian Pain Society - DE Moulin; AJ Clark; I Gilron; MA Ware; CPN Watson; BJ Sessle; T Coderre; PK Morley-Forster; J Stinson; A Boulanger; P Peng; GA Finley; et al. (Pain Research and Management)
Neuropathic pain (NeP), generated by disorders of the peripheral and central nervous system, can be particularly severe and disabling. Prevalence estimates indicate that 2% to 3% of the population in the developed world suffer from NeP, which suggests that up to one million Canadians have this disabling condition. Evidence-based guidelines for the pharmacological management of NeP are therefore urgently needed. Randomized, controlled trials, systematic reviews and existing guidelines focusing on the pharmacological management of NeP were evaluated at a consensus meeting. Medications are recommended in the guidelines if their analgesic efficacy was supported by at least one methodologically sound, randomized, controlled trial showing significant benefit relative to placebo or another relevant control group. Recommendations for treatment are based on degree of evidence of analgesic efficacy, safety, ease of use and cost-effectiveness. Analgesic agents recommended for first-line treatments are certain antidepressants (tricyclics) and anticonvulsants (gabapentin and pregabalin). Second-line treatments recommended are serotonin noradrenaline reuptake inhibitors and topical lidocaine. Tramadol and controlled-release opioid analgesics are recommended as third-line treatments for moderate to severe pain. Recommended fourth-line treatments include cannabinoids, methadone and anticonvulsants with lesser evidence of efficacy, such as lamotrigine, topiramate and valproic acid. Treatment must be individualized for each patient based on efficacy, side-effect profile and drug accessibility, including cost. Further studies are required to examine head-to-head comparisons among analgesics, combinations of analgesics, long-term outcomes, and treatment of pediatric and central NeP.